Amido resistente no arroz: papel do beneficiamento e do HMT combinado com ácido cítrico - Silva, Rogério de Jesus (2020)
Resistant starch has been considered an important prebiotic substance, as it can promote the selectivity of beneficial microorganisms in the intestine, as well as enable the production of short chain fatty acids by these probiotics. The processing of rice dramatically reduces the fiber content of the grain, which in turn is considered to be the basis of food for human consumption. In this sense, the objective of this work was to improve the starch content directly in rice grains, evaluating the processing steps (polishing and parboiling) and the application of HMT (Heat-moisture treatment) alone or in conjunction with acid treatment. In the first experiment, they were formulated as follows: polished rice (PR), brown (BR), parboiled (PP) and parboiled brown (PB). Then, all of them were submitted to HMT treatment combined with 0.2 Mol l-1 citric acid (HMTca) and encoded TPR (PR + HMTca), TBR (BR + HMTca), TPP (PP + HMTca) and TPB (PB + HMTca). In this step, it was obtained: amylose content; resistant starch (RS), non-resistant starch (NRS) and total starch (TS); color; cooking quality (optimal cooking time - OCT, loss of solids, water absorption - WA and volume expansion coefficient - VEC). Caravera rice showed 13.02% amylose. The resistant starch content ranged from 0.22% (BR) to 4.82% (TPP), the content of non-resistant starch was 78.70% (TPP) to 84.68% (PR) and that of starch total from 81.10% (TPP) to 85.06% (PR). In addition, TPR was the treatment that showed the greatest loss of PR through cooking (~ 53.8%). The TPB increased ~ 15.7 % due to cooking in the RS content. The OCT varied from 17.33 to 27.52 minutes, the loss of solids from 4.69% to 16.83%, the water absorption from 195.29 to 266.20 % and the CEV varied from 2.66 to 3.12 g g-¹. Reduction in clarity (L), increase in redness (a *) and non-yellowing (b *). Parboiling and HMTca increase RS, however, cooking reduced the RS content in most of the sample, except for BR and TPB (both integrals). Because the TPP sample had the highest mean for RS, it was chosen to assess the effect of citric acid concentration on the treatment of grains. The rules of 0.1 were applied; 0.2; 0.3; 0.4; 0.5 and 0.6 Mol l-1 e, named HMTac-1, 2, 3, 4, 5 and 6, in addition to the standard sample (HMTac-0) in which only HMT was sent using distilled water. The analyzes were analyzed: quality of cooking; texture; proximate composition; color; gelatinization and resistant starch. HMTac affected OCT, however, between the practices of acid no difference, water absorption reduced and the loss increased from 6.96% to 23.35%. Regarding texture, cohesiveness was not influenced, in elasticity only HMTac-6 differed from the other treatments and hardness of rice grains increased as a function of the acid dosage (from 10.45 N to 17.68 N). As for the chemical composition, proteins and fats were reduced. In color, the clarity (L) and yellowing (b *) decreased, and the redness was greater in HMTac-1, but the increase in the citric acid dosage reduced these values. In turn, cooking reduced the effects of HMTca on color. The temperature range of gelatinization was increased and the required energy (ΔH) was also greater. The RS content increased 93% in HMTac-6 (5.77%) in relation to the untreated sample (HMTca-0) (2.99 %). In addition, the AR values of Experiment 2 are for cooked rice, this represents a 50% increase in HMTca-6 (5.77%) compared to TPP (3.77%), sample from Experiment 1. Thus, from these experiments it was possible to verify that there was nutritional improvement in the rice grains of the variety BRSMG Caravera in its consumption (cooked) form, being added to future studies to evaluate its health benefits.